2022
DOI: 10.1007/s10899-021-10101-7
|View full text |Cite
|
Sign up to set email alerts
|

The Gambling Behaviour and Attitudes to Sports Betting of Sports Fans

Abstract: Survey responses from a sample of nearly 15,000 Australian sports fans were used to study the determinants of: (i) gambling behaviour, including if a person does gamble and the type of gambling engaged with; (ii) the number of sports and non-sports bets made over a 12-month period; and (iii) attitudes towards betting on sports. The probability of betting on sports decreased with increasing age and was lower for women and people with a university education. This gender difference varied with age, with the great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Yet, interestingly, risk conditional on frequency of play for sports (0.068) is almost double that of race betting (0.038). This may reflect the younger and less experienced demographic who are attracted to sports betting ( Hing et al., 2016 ; Seal et al., 2022 ), social and cultural differences ( Nyemcsok, Pitt, Kremer, & Thomas, 2022 ; Raymen & Smith, 2020 ), and/or the intense marketing and incentives currently associated with sports betting ( Browne, Rockloff, et al., 2019 ; Hing, Russell, Thomas, & Jenkinson, 2019 ; Rockloff, Browne, Russell, Hing, & Greer, 2019 ) contributing to more intensive gambling on sports. However, the prevalence of race betting is about double that of sports betting, giving rise to a similar degree of impact at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, interestingly, risk conditional on frequency of play for sports (0.068) is almost double that of race betting (0.038). This may reflect the younger and less experienced demographic who are attracted to sports betting ( Hing et al., 2016 ; Seal et al., 2022 ), social and cultural differences ( Nyemcsok, Pitt, Kremer, & Thomas, 2022 ; Raymen & Smith, 2020 ), and/or the intense marketing and incentives currently associated with sports betting ( Browne, Rockloff, et al., 2019 ; Hing, Russell, Thomas, & Jenkinson, 2019 ; Rockloff, Browne, Russell, Hing, & Greer, 2019 ) contributing to more intensive gambling on sports. However, the prevalence of race betting is about double that of sports betting, giving rise to a similar degree of impact at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-nationally, males tend to engage in sports betting to a much greater degree than females in both the general population (Labrador & Vallejo-Achón, 2020; Seal et al, 2022; Valenciano-Mendoza et al, 2023) and among individuals who gamble (Hing et al, 2017; Nower & Caler, 2019; Williams, Leonard, Belanger, Christensen, El-Guebaly, Hodgins, McGrath, Nicoll, & Smith, 2021; Wood & Williams, 2011). Further, gamblers who engage in sports betting also tend to be younger in age (Nower & Caler, 2019; Williams, Leonard, Belanger, Christensen, El-Guebaly, Hodgins, McGrath, Nicoll, & Smith, 2021), have single relationship status (Mestre-Bach et al, 2022), be employed (Winters & Derevensky, 2019), and have high levels of education (Mestre-Bach et al, 2022; Williams, Leonard, Belanger, Christensen, El-Guebaly, Hodgins, McGrath, Nicoll, & Smith, 2021; Winters & Derevensky, 2019) compared to those who do not engage in sports betting.…”
Section: Characteristics Of People Who Bet On Sportsmentioning
confidence: 99%
“…Although sports betting is generally perceived as low risk by those engaged in it (Seal et al, 2022), there is evidence to suggest that sports betting can be linked to a variety of harms. For instance, sports betting behavior is associated with financial harms such as overspending (Gathoni et al, 2021).…”
Section: Characteristics Of People Who Bet On Sportsmentioning
confidence: 99%
“…In a recent study, Seal et al (2022) reported that sports betting is seen as innocuous, widespread, and an important element of enjoying sports, especially among young males. Its influence on the normalization of gambling, particularly among the young, has been a growing source of worry in nations such as Australia and the United Kingdom during the last decade (Purves et al, 2020).…”
Section: Adolescents Sports Gamblingmentioning
confidence: 99%